Premature atrial contractions: A predictor of atrial fibrillation and a relevant marker of atrial cardiomyopathy - Guichard, Jean-Baptiste; Guasch, Eduard; Roche, Frederic; Da Costa, Antoine; Mont, Lluís (Frontiers in Physiology, 2022)
An increased burden of premature atrial contractions (PACs) has long been considered a benign phenomenon. However, strong evidence of their involvement in the occurrence of atrial fibrillation (AF), ischemic stroke, and excess mortality suggests the need for management. The central question to be resolved is whether increased ectopic atrial rhythm is only a predictor of AF or whether it is a marker of atrial cardiomyopathy and therefore of ischemic stroke. After reviewing the pathophysiology of PACs and its impact on patient prognosis, this mini-review proposes to 1) detail the physiological and clinical elements linking PACs and AF, 2) present the evidence in favor of supraventricular ectopic activity as a marker of cardiomyopathy, and 3) outline the current limitations of this concept and the potential future clinical implications.